1992
DOI: 10.1177/154193129203600506
|View full text |Cite
|
Sign up to set email alerts
|

A Methodological Taxonomy for Warnings Research

Abstract: Beginning with several empirical papers in the late 1970's, there has been considerable research concerned with assessing the effectiveness of such attempted safety interventions as on-product warnings and safety signs. The focus of research on warnings has shifted from a debate on whether warnings work to systematic investigation of the factors that do or could influence safety-related product-user behavior. From the perspective of safety, the logical test of a warning must be reduction of the frequency and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…As a step beyond the taxonomy developed by Ayres et al (1992), each study was further categorized by its dependent measure based on whether the study measured behavioral compliance and/or intention/predicted likelihood of compliance. The latter (intention/predicted likelihood of compliance) was further subdivided by whether the study measured participants’ predictions of their own compliance (i.e., intentions) or participants’ predictions of the likelihood of compliance of others.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a step beyond the taxonomy developed by Ayres et al (1992), each study was further categorized by its dependent measure based on whether the study measured behavioral compliance and/or intention/predicted likelihood of compliance. The latter (intention/predicted likelihood of compliance) was further subdivided by whether the study measured participants’ predictions of their own compliance (i.e., intentions) or participants’ predictions of the likelihood of compliance of others.…”
Section: Methodsmentioning
confidence: 99%
“…Each included study was categorized according to the methodological taxonomy developed by Ayres, et al (1992). Categories distinguished between studies that were conducted in a laboratory (or other contrived environment) versus experiments or observations conducted in real-world situations with unsuspecting participants.…”
Section: Categorizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The studies selected for review -laboratory, out-of-order signs, or safety warnings outside the laboratory -can have a major effect on conclusions reached about the behavioral effectiveness of warnings; in particular, reviews based on real-world behavioral results have found little evidence of effectiveness (e.g. Ayres et al, 1992;Ayres et al, 1998), whereas reviews based primarily on laboratory studies are more optimistic (Cox et al, 1997;Argo & Main, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Taxonomies have been developed to help researchers and practitioners better understand various issues such as pedestrian injuries (Schofer et al, 1995), safety-related work behavior (DeJoy, 1993), warnings (Ayres, Gross, Horst, & Robinson, 1992), mental models (Moray, 1996), pilot training tasks (Meyer, Laveson, Weissman, & Eddowes, 1975), and web design (Cheong & Shehab, 2003) to name a few. However, the development of detailed taxonomies for driverrelated issues is not as abundant.…”
Section: Introduction Backgroundmentioning
confidence: 99%